The Evolution of Mixed Methods Research: Integrating Qualitative and Quantitative Approaches - T.V.S. Padmaja (AG Volumes, 2024)
Mixed methods research (MMR) is a method that combines qualitative and quantitative methods to offer a comprehensive understanding of intricate research questions. The development of MMR from its early foundations of combining methodologies is the focus of this review, which traces its evolution. A discussion of a variety of mixed-method research designs, such as convergent parallel, explanatory, exploratory, and embedded designs. In spite of the advantages, the “integration of qualitative and quantitative approaches” presents a variety of challenges, including the need to ensure methodological rigour, the resource-intensive nature of the process, the complexity of the design, and communication differences.